The image quality of ion computed tomography at clinical imaging dose levels. Issue 11 (20th October 2014) - Hansen, David C.; Bassler, Niels; Sørensen, Thomas Sangild; Seco, Joao
Abstract : Purpose: Accurately predicting the range of radiotherapy ions in vivo is important for the precise delivery of dose in particle therapy. Range uncertainty is currently the single largest contribution to the dose margins used in planning and leads to a higher dose to normal tissue. The use of ion CT has been proposed as a method to improve the range uncertainty and thereby reduce dose to normal tissue of the patient. A wide variety of ions have been proposed and studied for this purpose, but no studies evaluate the image quality obtained with different ions in a consistent manner. However, imaging doses ion CT is a concern which may limit the obtainable image quality. In addition, the imaging doses reported have not been directly comparable with x‐ray CT doses due to the different biological impacts of ion radiation. The purpose of this work is to develop a robust methodology for comparing the image quality of ion CT with respect to particle therapy, taking into account different reconstruction methods and ion species. Methods: A comparison of different ions and energies was made. Ion CT projections were simulated for five different scenarios: Protons at 230 and 330 MeV, helium ions at 230 MeV/u, and carbon ions at 430 MeV/u. Maps of the water equivalent stopping power were reconstructed using a weighted least squares method. The dose was evaluated via a quality factor weighted CT dose index called the CT dose equivalent index (CTDEI). Spatial resolution was measured by the modulation transfer function. This was done by a noise‐robust fit to the edge spread function. Second, the image quality as a function of the number of scanning angles was evaluated for protons at 230 MeV. In the resolution study, the CTDEI was fixed to 10 mSv, similar to a typical x‐ray CT scan. Finally, scans at a range of CTDEI's were done, to evaluate dose influence on reconstruction error. Results: All ions yielded accurate stopping power estimates, none of which were statistically different from the ground truth image. Resolution (as defined by the modulation transfer function = 10% point) was the best for the helium ions (18.21 line pairs/cm) and worst for the lower energy protons (9.37 line pairs/cm). The weighted quality factor for the different ions ranged from 1.23 for helium to 2.35 for carbon ions. For the angle study, a sharp increase in absolute error was observed below 45 distinct angles, giving the impression of a threshold, rather than smooth, limit to the number of angles. Conclusions: The method presented for comparing various ion CT modalities is feasible for practical use. While all studied ions would improve upon x‐ray CT for particle range estimation, helium appears to give the best results and deserves further study for imaging.